A novel Meloidogyne incognita chorismate mutase effector suppresses plant immunity by manipulating the salicylic acid pathway and functions mainly during the early stages of nematode parasitism. (15th March 2018) - Wang, X.; Xue, B.; Dai, J.; Qin, X.; Liu, L.; Chi, Y.; Jones, J. T.; Li, H.
Abstract : Meloidogyne incognita is the most economically important plant‐parasitic nematode. Meloidogyne incognita manipulates plant cell development and metabolism by injecting effectors from the oesophageal glands into the plant host. Chorismate mutase (CM) is one such effector that may contribute to successful parasitism by M. incognita . This investigation identified and functionally characterized a novel CM effector, Mi‐CM‐3, which is more similar to CMs from bacteria than from other phytoparasitic nematodes. Spatial and temporal expression assays showed Mi‐cm‐3 mRNA accumulates specifically in the subventral oesophageal glands and transcription is up‐regulated during the early parasitic stages of the nematode. In planta gene silencing of Mi‐cm‐3 attenuated nematode parasitism. In addition, Mi‐cm‐3 could fully restore the full virulence phenotype of the pathogenic bacterium Xanthomonas oryzae pv. oryzae by complementation when it was introduced into a mutant strain carrying a deletion in the CM gene. Transient expression of Mi‐CM‐3 caused a reduction in levels of salicylic acid (SA) and mRNA of gene PR1 in Nicotiana benthamiana in response to oomycete pathogen Phytophthora capsici infection, while confocal observations showed that Mi‐CM‐3 was localized within the cytoplasm and the nucleus, but not the plastids, of transfected N. benthamiana leaf cells. Constitutive expression of Mi‐CM‐3 in N. benthamiana plants inhibited root growth and increased susceptibility to M. incognita infection. These results provide direct experimental evidence to show that Mi‐CM‐3 may play an important role in suppressing plant immunity by regulating the SA pathway during the early parasitic stage of M. incognita so as to promote nematode parasitism.